PEMBELAJARAN MASA LALU DENGAN MEDIA PEMBELAJARAN MASA KINI MENUJU MASA DEPAN GENERASI EMAS - Magelhaes Mendur; Saliman Saliman; Khofifah Nur Rahmah (STKIP Singkawang, 2026)
Technological development is a challenge of the times that has an impact on human life. The urgency of history learning, which shapes students, is only viewed with disdain due to boredom and monotony. It is this negative stigma that needs to be improved so that the paradigm of learning history, such as how history itself is valuable, can be changed. This research will later examine how history learning uses social media-based learning media at SMA N 1 Kawangkoan. Therefore, this research employs a qualitative approach with a case study research design. Ultimately, using a case study approach, this research reveals how history learning at SMA N 1 Kawangkoan utilizes social media technology as a learning medium. This research ultimately revealed that the implementation of history learning at SMA N 1 Kawangkoan is adapted to the conditions of the classroom and school, and that limited facilities and teacher capabilities pose challenges to the use of social media as a learning medium. Nevertheless, history learning at SMA N 1 Kawangkoan is fully supported by the school in the implementation of social media-based learning media. Therefore, the school continues to improve itself regarding existing shortcomings. Learning from the past must continue to improve with current learning media to move toward the future.